Bankrupted Detroit. (April 2014) - Desan, Mathieu Hikaru
The recent declaration of the largest municipal bankruptcy in US history has propelled Detroit's plight into the international spotlight. Though a victim of the general decline of US manufacturing, drawing on Thomas Sugrue's pioneering work I argue that Detroit's crisis is better understood as a specifically urban crisis. The city's concentrated poverty and desolation and its fiscal straits are not reducible to broader economic trends, nor are they exclusively the product of political mismanagement. Rather, they are the outcome of a long history of economic decentralization and racial segregation, made worse by a politico-administrative arrangement that distributes wealth and services unequally across the metropolitan area. By imposing municipal austerity, Detroit's bankruptcy is unlikely to do much to address these fundamental inequalities. Any plan to revitalize the city must move beyond boosterism and tackle head on the problems of racial and economic segregation that continue to affect Detroit's 700, 000 residents.